DYNASTIC TIES OF DAGESTANI FEUDAL FAMILIES AS A FACTOR IN FIGHTING THE INVASION OF NADIR SHAH - Polcaeva, Fatimat Abdulnetifovna (History, Archeology and Ethnography of the Caucasus, 2022)
Based on the analyzed information from various sources and a wide range of literature, the author makes an attempt to assess the significance of the dynastic ties of the Dagestan rulers in organizing a joint struggle against the Iranian conquest in the 18th century, to determine the role of political marriage in the relationship of local rulers. To achieve this goal, the study consideres a number of key issues, from which particular conclusions are drawn. The work applies general scientific and specific methods. When restoring dynastic ties, the information from written sources was critically analyzed. To structure the work, a typological method was used, which made it possible to group the information obtained. By examining the political and administrative map of the region, the potential complexity of the political relations of local dynasties that formed over the centuries in a tight space has been shown. In the context of global history, the ways of forming family ties between royal houses are determined: the presence of a common ancestor of the Dagestan dynasties, the separation of an independent branch of the dynasty through conflict, the peaceful division of the state between heirs, followed by the separation of independent dynasties, and the conclusion of political marriages. The same universal formula is used by the author to restore family ties between the Dagestan dynasties (Shamkhals of Tarky, Kaitag Utsmis, Kazikumukh, Quba and Avar khans) and their neighbors. Special attention is paid to the restoration of dynastic ties during the invasion of the Iranian conqueror Nadir Shah in the 18th century. Analyzing political alliances in the context of dynastic ties, the author considers the role of political marriage in organizing a joint struggle against the Iranian ruler. The study allows us to draw conclusions about the significant role of political marriage as a tool of diplomacy, but far from having a decisive role in specific historical events.